2014
DOI: 10.1089/end.2013.0534
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve Assessment of Robot-Assisted Radical Prostatectomy Compared with Open-Surgery Controls from the Premier Perspective Database

Abstract: Introduction: The primary aims of this study were to assess the learning curve effect of robot-assisted radical prostatectomy (RARP) in a large administrative database consisting of multiple U.S. hospitals and surgeons, and to compare the results of RARP with open radical prostatectomy (ORP) from the same settings. Results: The mean surgery time was longer for RARP (4.4 hours, standard deviation [SD] 1.7) compared with ORP (3.4 hours, SD 1.5) in the same hospitals ( p < 0.0001). Inpatient stay was shorter for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 26 publications
6
29
1
2
Order By: Relevance
“…It is known from the literature that robotic surgery requires a certain learning curve and clinical success correlates with case numbers [35]. In this study, the number of surgeons performing open and robotic-assisted prostatectomy differed, while the three surgeons of the robotic-cohort were experienced both in open and robotic-assisted prostatectomy.…”
Section: Discussionmentioning
confidence: 96%
“…It is known from the literature that robotic surgery requires a certain learning curve and clinical success correlates with case numbers [35]. In this study, the number of surgeons performing open and robotic-assisted prostatectomy differed, while the three surgeons of the robotic-cohort were experienced both in open and robotic-assisted prostatectomy.…”
Section: Discussionmentioning
confidence: 96%
“…In certain disciplines, most notably urology and gynecology (prostatectomy made up 31 % and hysterectomy 41 % of all da Vinci Ò procedures in 2011), robotic surgical systems have enabled increased adoption of minimally invasive techniques by surgeons and a move away from open surgery. When compared with open prostatectomy, minimally invasive robotic prostatectomy has been demonstrated to be associated with better urinary continence and erectile function recovery, lower rates of positive surgical margins, and better perioperative outcomes [5][6][7]. However, when an established laparoscopic approach to an operation exists, the benefits of robotic surgery when compared with laparoscopy have not been demonstrated to be superior [8,9].…”
Section: Technology Significancementioning
confidence: 99%
“…[15] Similarly, in a study examining 27,348 RARP performed by 744 surgeons using an administrative inpatient and outpatient database (Premier Research Perspective Database), surgeons further along their learning curve showed significant improvements in surgery time, hospital stay, conversion rates, and complication rates. [15,16]. We found that the year of operation was a significant predictor of requiring a blood transfusion within the RARP group only; with patients undergoing surgery in 2009 or earlier having a significantly higher risk of needing transfusion compared to later years.…”
Section: Discussionmentioning
confidence: 76%